Multi-criteria feasibility assessment of cost-optimized alternatives to comply with heating demand of existing office buildings – A case study. (15th November 2019) - Walker, Shalika; Katic, Katarina; Maassen, Wim; Zeiler, Wim
Abstract: In line with the EU's goal to phase out the use of fossil fuel, the Dutch government is determined to have gas-free new buildings from 2018 onwards. However, with over 90% of the heating demand in both existing residential and commercial buildings currently accomplished with natural gas, transitioning to a gas-free system in existing buildings remains an enormous challenge. Though electric heat pumps are gaining large ground as a substitute, the increase in electricity consumption also introduces uncertainties and further complexities to an already constrained electricity grid. This paper thus evaluates, the impact of switching to a greener demand side with all-electric heating systems for existing characteristics of the office buildings, with the current composition of the electricity production side in the Netherlands. Using multi-objective computational simulations with linear programming and feasibility assessment using the Kesselring method, the study reveals hybrid energy systems (utilizing electricity and gas) favors over all-electric energy systems for fulfilling the heating demand when the buildings are considered individually. This is because the switch to a greener heating system using electricity translates to a shift of demand for fossil energy from the building side to the central production side for the on-going situation in the Netherlands. Highlights: The influence of gas-free transition on individual existing buildings is discussed. Importance of including feasibility assessment is highlighted. Hybrid and all-electric scenarios for a case study office building is demonstrated. The results are benchmarked with the government regulations in the Netherlands. Shift of fossil-energy demand from the building to the production side is observed.